Sphagnum sect. Squarrosa (Sphagnaceae, Musci) en la Península Ibérica. - Fuertes Lasala, Esther; Munín, Estrella (Botanica Complutensis, 2001)
MUNÍN, E. & FUERTES, E. 2001. Sphagnum sect. Squarrosa (Sphagnaceae, Musci) in the Iberian Peninsula. Bot. Complutensis 25: 271-287. Sphagnum sect. Squarrosa is represented by the species Sphagnum squarrosum and S. teres in Spain both are restricted to oligotrofic, wet habitats in high mountains from the Iberian Peninsula. The SEM photographs leaves and the distribution maps of each taxon are reported.